Germ cell cancer in pregnancy - Successfully treated with chemotherapy and surgery - A. Sharma; I. Reid; A. Gogbashian; B. Kaur; C. Fotopoulou (Elsevier, 2023)
A 31-year-old primigravida, with spontaneous singleton pregnancy, presented in 21 weeks of gestation with abdominal pain. Abdominal ultrasound (USS) and Magnetic Resonance Imaging (MRI) showed a 12 × 14cm large complex lesion arising from the right ovary suspicious for an ovarian malignancy. The radiological staging demonstrated no further metastatic disease; however, it also revealed a 6 cm lesion in the contralateral ovary, consistent with a dermoid cyst. After tumour board discussion the patient underwent a mid-line laparotomy with right oophorectomy, cytology, and peritoneal and omental staging, under oral tocolysis with indomethacin. The left presumed ovarian dermoid was left in situ to avoid additional surgical and obstetrical morbidity. Histology confirmed a grade 3 immature teratoma with primitive neuroepithelium focally present on the capsular surface and atypical cells in the cytology amounting to a stage 1 C2 disease at least. Due to high-risk disease, she was offered adjuvant treatment. The patient received one cycle of intravenous paclitaxel, etoposide, and cisplatin chemotherapy, in an adjuvant setting. She underwent an elective caesarean section at 36 weeks, with the safe delivery of a healthy baby girl. After 6 weeks of her delivery, she received three further cycles of etoposide, and cisplatin to complete her course of adjuvant chemotherapy. Three months after the last chemotherapy cycle, she underwent a laparoscopic removal of the left ovarian dermoid that had increased in size to 8 cm. Final histology revealed no immature elements. To this point, 2 years after initial diagnosis, both mother and child are healthy with no long-term complications. The patient has resumed her normal menstrual cycle and being in remission, she wishes soon to try for a second child. To our knowledge, this is the only reported case of ovarian immature teratoma in pregnancy treated successfully with surgery and adjuvant iv paclitaxel, etoposide, and cisplatin chemotherapy regime.